2020
DOI: 10.3390/app10020681
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Shifting Quality of the CVT Tractor under Hydraulic System Failure

Abstract: The failure of a hydraulic system will affect the shifting quality and driving safety of a CVT tractor. In order to reveal the response of the tractor under different hydraulic system failures without destroying the transmission, the following methods are proposed in this paper: firstly, building the simulation model of CVT; secondly, building a test bench to test and verify the transmission model to ensure that the simulation model can accurately predict the response of CVT under different clutch oil pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(29 reference statements)
0
4
0
1
Order By: Relevance
“…There are many indicators available for evaluating the quality of the shifting process, such as shifting time, jerk amplitude, interior noise level, and acceleration characteristics. Previous studies have found that jerk and shifting time play a decisive role in shift quality [33][34][35][36]. The control requirements of this study are fast shift time, low jerk, and smooth output torque at the wheel.…”
Section: B Control Requirementmentioning
confidence: 94%
See 1 more Smart Citation
“…There are many indicators available for evaluating the quality of the shifting process, such as shifting time, jerk amplitude, interior noise level, and acceleration characteristics. Previous studies have found that jerk and shifting time play a decisive role in shift quality [33][34][35][36]. The control requirements of this study are fast shift time, low jerk, and smooth output torque at the wheel.…”
Section: B Control Requirementmentioning
confidence: 94%
“…𝑲(π‘˜) = 𝑷 βˆ’ (π‘˜)𝑯 𝑻 [𝑯𝑷 βˆ’ (π‘˜)𝑯 𝑻 + 𝑹] βˆ’πŸ (33) 𝒙 ̂𝒂(π‘˜) = 𝒙 Μ‚π‘Ž βˆ’ (π‘˜) + 𝑲(π‘˜)[𝒛(π‘˜) βˆ’ 𝑯𝒙 Μ‚π‘Ž βˆ’ (π‘˜)](34)𝑷(π‘˜) = [𝑰 βˆ’ 𝑲(π‘˜)𝑯]𝑷 βˆ’ (π‘˜)(35) …”
unclassified
“…According to different design principles, different clutch architectures have been devised such as friction clutch 2 , 3 , Electro mechanically clutch taking motor as power source 4 , 5 , hydraulic or electro hydraulic clutch 6 , 7 and electro pneumatic clutch 8 , 9 . To realize clutch engagement or disengagement control, clutch chamber pressure, transmission torque and clutch piston displacement are the mostly used control modes.…”
Section: Introductionmentioning
confidence: 99%
“…In the referenced literatures, different clutch architectures have been proposed and different driving sources for the clutch actuator are designed for automated manual transmissions. 3 – 5 Electro mechanically actuator taking motor as power source is widely adopted in commercial cars or small and mid-sized vehicles. Hydraulic manipulator or electro hydraulic manipulator is an alternative drive form for the automatic mechanical transmission system not only used on the wheeled agricultural tractors but also on the heavy-duty automobile vehicles.…”
Section: Introductionmentioning
confidence: 99%